The Impact Of Flexitime On Motivation And Work Performance Of Health Workers In Zimbabwe: Evidence From Parirenyatwa Group Of Hospitals - Chiware, Mervis; Gweshe, Tapiwa Gay; Kanodeweta, Freeman; Maiwasha, Babra; Muronza, Caroline (Advances in Social Sciences Research Journal, 2021)
This article studies the impact of flexitime on health workers’ motivation and work performance at Parirenyatwa Group of Hospitals. Despite the positive contribution of flexitime on motivation and work performance, adequate academic articles are yet to be published in Zimbabwe’s public sector on this subject. The thrust of this article was to close this gap in knowledge by determining the impact of flexitime on motivation and work performance at Parirenyatwa Group of Hospitals. Emailed self-administered questionnaires, telephone interviews as well as documentary research were used to find out the relationship between flexitime, motivation and work performance. Results from the research painted a close relationship between flexitime motivation and work performance. The study indicated that flexitime improves work- life balance and the physical health of the health workers at Parirenyatwa Group of Hospitals. Organisational commitment evidenced by reduced absenteeism was also achieved due to the implementation of flexitime. Flexitime requires professional administration and top management support for best results. The Ministry of Health and Child Care should adopt flexitime as a long term policy to motivate employees and line managers require adequate training to implement flexitime.